Cardiovascular Magnetic Resonance Demonstrates Reversible Atrial Dysfunction After Catheter Ablation of Persistent Atrial Fibrillation. (29th March 2013) - MUELLERLEILE, KAI; GROTH, MICHAEL; STEVEN, DANIEL; HOFFMANN, BORIS A.; SARING, DENNIS; RADUNSKI, ULF K.; LUND, GUNNAR K.; ADAM, GERHARD; ROSTOCK, THOMAS; WILLEMS, STEPHAN
Reversible Dysfunction After Persistent AF Ablation Introduction There is a paucity of data on atrial injury following ablation of persistent atrial fibrillation (AF). This study aimed at assessing reversibility of atrial dysfunction after successful persistent AF ablation using cardiovascular magnetic resonance (CMR). Methods and Results CMR was performed during sinus rhythm (SR) in 20 consecutive patients with persistent AF at baseline (BL) within 24 hours after ablation and after 6‐month follow‐up (FU). Catheter ablation included atrial substrate modification using the stepwise approach following pulmonary vein isolation (PVI) in order to attempt termination of persistent AF. Active left (LA) and right atrial (RA) function were quantified by calculating the active emptying fraction (AEF) from transvalvular flow profiles using velocity encoded (VENC) CMR. LA appendage (LAA) function was quantified by measurements of peak a‐wave velocities from flow profiles perpendicular to the LAA orifice. Peri‐atrial edema was assessed using black‐blood T2‐weighted CMR. A significant improvement was found in LA‐AEF from 18 (12–26)% at BL to 25 (22–35)% at FU (P = 0.0001). Furthermore, RA‐AEF significantly increased from 31 (19–35)% at BL to 40 (35–51)% at FU (P < 0.0001). A significant improvement was also found for LAA a‐wave velocities from 45 (31–65) cm/s at BL to 62 (49–75) cm/s at FU (P < 0.01). The area of peri‐atrial edema on T2‐weighted CMR decreased from 1393 (1098–1797) mm2 at BL to 24 (1–92) mm2 at FU (P < 0.0001). Conclusion CMR demonstrates reversibility of LA, LAA, and RA dysfunction associated with resorption of peri‐atrial edema in patients with SR after persistent AF ablation.